2021
DOI: 10.3390/metabo11080563
|View full text |Cite
|
Sign up to set email alerts
|

PRM-MS Quantitative Analysis of Isomeric N-Glycopeptides Derived from Human Serum Haptoglobin of Patients with Cirrhosis and Hepatocellular Carcinoma

Abstract: Currently, surveillance strategies have inadequate performance for cirrhosis and early detection of hepatocellular carcinoma (HCC). The glycosylation of serum haptoglobin has shown to have significant differences between cirrhosis and HCC, thus can be used for diagnosis. We performed a comprehensive liquid chromatography—parallel reaction monitoring—mass spectrometry (LC-PRM-MS) approach, where a targeted parallel reaction monitoring (PRM) strategy was coupled to a powerful LC system, to study the site-specifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 25 publications
(20 citation statements)
references
References 36 publications
1
11
0
Order By: Relevance
“…It was further shown that when AFP was combined with glycopeptides N207_A3G3F1S2 and N207_A3G3F1S2 as a 3-marker panel, the result provided a better AUC value than AFP alone. 46 Different from this work, the current work contains a total of 95 patients’ serum samples in a larger sample set and the precursor ions selected in our current experiment were based on our previous work 22 , 23 where both charge states 3 and 4 precursor ions were included. These differences would provide more accurate and precise results, which include significant changes of glycopeptides in abundance involving sites N184 and N241.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was further shown that when AFP was combined with glycopeptides N207_A3G3F1S2 and N207_A3G3F1S2 as a 3-marker panel, the result provided a better AUC value than AFP alone. 46 Different from this work, the current work contains a total of 95 patients’ serum samples in a larger sample set and the precursor ions selected in our current experiment were based on our previous work 22 , 23 where both charge states 3 and 4 precursor ions were included. These differences would provide more accurate and precise results, which include significant changes of glycopeptides in abundance involving sites N184 and N241.…”
Section: Resultsmentioning
confidence: 99%
“…In a recent work, it has been reported that four glycopeptides involving site N207 of Hp changes significantly in abundance between HCC and cirrhosis from a total of 30 patients’ serum samples. It was further shown that when AFP was combined with glycopeptides N207_A3G3F1S2 and N207_A3G3F1S2 as a 3-marker panel, the result provided a better AUC value than AFP alone . Different from this work, the current work contains a total of 95 patients’ serum samples in a larger sample set and the precursor ions selected in our current experiment were based on our previous work , where both charge states 3 and 4 precursor ions were included.…”
Section: Resultsmentioning
confidence: 99%
“…With the aforementioned dissociation techniques, several acquisition strategies can be used to improve the quantitation of glycans and glycopeptides. Multiple reaction monitoring (MRM) and recently parallel reaction monitoring (PRM) have been demonstrated to be accurate targeted quantitation methods for both glycans and glycopeptides [178][179][180][181]. The limitation of MRM and PRM is that they cannot be used for untargeted analysis.…”
Section: Dissociation and Acquisition Techniques Facilitate Ms-based ...mentioning
confidence: 99%
“…Another advantage of PRM is that it enables the monitoring of all fragment ions simultaneously, thus allowing the selection of any fragments for quantitation. The MRM for glycomic analysis has been demonstrated ( Zhou et al, 2015 ), while PRM has been proved in a glycoproteomic study ( Gutierrez Reyes et al, 2021 ). The pitfall of both MRM and PRM is that they cannot be utilized in untargeted glycomic analysis, thus limiting their use in initial glycomic studies of CNS diseases.…”
Section: Mass Spectrometry-based Fragmentation Techniques Facilitate ...mentioning
confidence: 99%